Prensa escrita y su influencia en el desarrollo cultural en los habitantes de la Parroquia San Cristóbal, Cantón Quevedo año 2019 - Gonzales Jiménez, Selena Carolina (2019)
The present investigation of the written press and its influence on cultural development is very important because it includes certain representations of culture that are built in the usual journalistic work. Although many times it is not given the social interest that it requires due to the lack of professionalization or because it is not of greater importance for citizens, but the culture frames the well-being of people to motivate them and empower us to preserve their roots and moral values , through methodological approaches, with the analysis of the variables and contents, it was possible to survey columnists and social communicators about the little information that is provided to culture, While it is true that cultural information is not so relevant, but in the different parishes and cantons of Ecuador if there are cultural events that lead to be promoted by all media. It is shown that cultural production and its development is permanent but it does not have the necessary reception by the written press, then setting precedents so that with different teaching strategies culture can be spread with great quality in all communities and have as great beneficiaries to children, adolescents so that they can transmit that legacy and not lose their cultural identity. Finally, the written press was one of the first means of communication that allowed readers to enjoy different activities that are immersed in their information, facilitating knowledge between cultures and the varied availability of options between: opinions, sports, chronic, social, children's, gastronomic and advertising spaces. Regarding what you want to achieve is to propose a cultural education program that allows you to mold and shape the different cultural events that contribute to the development of society.